Bảo hộ quyền sở hữu trí tuệ trong hiệp định TRIPS - Diển, Nguyễn Bá (VNU Journal of Science: Legal Studies; Vol 20 No 4, 2004)
Nowadays, intellectual property rights have played one of the most important parts in owner rights beside tangible property rights when the scientific - technological revolution has been renewing the world. Therefore, protecting intellectual property rights is both urgent and significant mission of each country in the process of integration into the economic world, and Vietnam does not except.The author focused to point out and analyze the basic principles of TRIPS. In addition, the author showed the Vietnam regulations and laws inadequate, which influence to the effectiveness on implementation of intellectual property rights in the comparative relation with TRIPS. In conclusion, the author proposed initial and long-term measures to perfect Vietnamese legal system on intellectual property rights to integrate rapider.